Molecular mechanisms of polarized transport to the apical plasma membrane - Kunii, Masataka; Harada, Akihiro (Frontiers in Cell and Developmental Biology, 2024)
Cell polarity is essential for cellular function. Directional transport within a cell is called polarized transport, and it plays an important role in cell polarity. In this review, we will introduce the molecular mechanisms of polarized transport, particularly apical transport, and its physiological importance.